Generation and Analysis of Expressed Sequence Tags from Olea europaea L. - Ozgenturk, Nehir Ozdemir; Oruc, Fatma; Sezerman, Ugur; Kucukural, Alper; Korkut, Senay Vural; Toksoz, Feriha; Un, Cemal (HINDAWI LTD, 2010)
Olive (Olea europaea L.) is an important source of edible oil which was originated in Near-East region. In this study, two cDNA libraries were constructed from young olive leaves and immature olive fruits for generation of ESTs to discover the novel genes and search the function of unknown genes of olive. The randomly selected 3840 colonies were sequenced for EST collection from both libraries. Readable 2228 sequences for olive leaf and 1506 sequences for olive fruit were assembled into 205 and 69 contigs, respectively, whereas 2478 were singletons. Putative functions of all 2752 differentially expressed unique sequences were designated by gene homology based on BLAST and annotated using BLAST2GO. While 1339 ESTs show no homology to the database, 2024 ESTs have homology (under 80%) with hypothetical proteins, putative proteins, expressed proteins, and unknown proteins in NCBI-GenBank. 635 EST's unique genes sequence have been identified by over 80% homology to known function in other species which were not previously described in Olea family. Only 3.1% of total EST's was shown similarity with olive database existing in NCBI. This generated EST's data and consensus sequences were submitted to NCBI as valuable source for functional genome studies of olive.
Keywords: OLIVE; DNA; EST; GENES; IDENTIFICATION; POLYMORPHISM; MARKERS; FRUIT; TOOL; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Genetics & Heredity